Theoretical insights into the oxidation of substrates by high-spin iron(III)-acylperoxido complexes - Velmurugan, Gunasekaran; Comba, Peter (European journal of inorganic chemistry, 2025)
While the oxidation of organic substrates by FeIV-oxido complexes has been studied extensively, there are only few highly reactive FeIII-alkylperoxido complexes. We report here computational mechanistic work of a novel mononuclear nonheme FeIII-phenylperoxido acetate complex, focusing on the splitting of the peroxide bond, the epoxidation of ethene and the hydroxylation of cyclohexane. Our results reveal that the peroxide bond undergoes homolysis, leading to the formation of an FeIV-oxido complex. Spectroscopic evidence supports the presence of an FeIV species, aligning with the observed product distribution. Additionally, we have explored a potential sigmatropic rearrangement mechanism. However, based on the activation barriers and initial product energy levels, the FeIII rather than the FeV species is shown to be the active species in the initial step. For both, the epoxidation and hydroxylation reactions, stepwise mechanisms are proposed, involving the FeIV-oxido species as the catalytic intermediate. The energy barriers calculated for these pathways are significantly lower than those for concerted mechanisms, involving the FeIII-peroxido species as direct oxidant. In particular, the calculated activation barrier in the FeIV-oxido pathway is 38 kJ/mol for the activation of the C=C bond in ethene, while the analogous step in the FeIII-peroxido pathway is calculated to be as high as 183 kJ/mol. Our computational results indicate that the FeIV-oxido species is the active catalyst in these oxidation reactions.